Glial regulation of critical period plasticity - Starkey, Jacob; Horstick, Eric J.; Ackerman, Sarah D. (Frontiers in Cellular Neuroscience, 2023)
Animal behavior, from simple to complex, is dependent on the faithful wiring of neurons into functional neural circuits. Neural circuits undergo dramatic experience-dependent remodeling during brief developmental windows called critical periods. Environmental experience during critical periods of plasticity produces sustained changes to circuit function and behavior. Precocious critical period closure is linked to autism spectrum disorders, whereas extended synaptic remodeling is thought to underlie circuit dysfunction in schizophrenia. Thus, resolving the mechanisms that instruct critical period timing is important to our understanding of neurodevelopmental disorders. Control of critical period timing is modulated by neuron-intrinsic cues, yet recent data suggest that some determinants are derived from neighboring glial cells (astrocytes, microglia, and oligodendrocytes). As glia make up 50% of the human brain, understanding how these diverse cells communicate with neurons and with each other to sculpt neural plasticity, especially during specialized critical periods, is essential to our fundamental understanding of circuit development and maintenance.